Immediate consequences and solutions used to maintain medical education during the COVID-19 pandemic for residents and medical students: a restricted review. Issue 1159 (1st April 2021) - Chasset, François; Barral, Matthias; Steichen, Olivier; Legrand, Anne
Abstract : Background: The COVID-19 outbreak has dramatically impacted medical education, both bedside and academic teaching had to be adapted to comply with the reorganisation of care and social distancing measures. Objectives: To overview the impact of the pandemic on medical education, including the pedagogical responses adopted and their assessment by medical students and residents. Material and methods: This restricted systematic review was performed using Rayyan QCRI, to select observational or interventional articles and field experience reports assessing the impact of the COVID-19 pandemic on medical education for medical students and residents. Study design, study population, geographical origin, use of an educational tools (including softwares and social media), their type and assessment, were recorded. For studies evaluating a specific tool the Medical Education Research Study Quality Instrument (MERSQI) was used to assess study quality. Results: The literature search identified 1480 references and 60 articles were selected. Most articles focused on residents (41/60; 69%), and half (30/60; 50%) involved surgical specialties. Online courses were the most frequently used pedagogical tool (52/60; 88%). Simulation tools were used more frequently in articles involving surgical specialties (15/29; 52%) compared with medical specialties (2/14; 12%) (p=0.01). Only four studies reported the assessment of pedagogical tools by medical students, their MERSQI scores ranged from 5.5/18 to 9.0/18. Conclusion: Medical education was highly impacted by the COVID-19 pandemic particularly in surgical specialties. Online courses were the most frequently attempted solution to cope with social distancing constraints. Medical students' assessment of pedagogical tools was mostly positive, but the methodological quality of those studies was limited.